2007
DOI: 10.1002/hon.829
|View full text |Cite
|
Sign up to set email alerts
|

R‐CHOP‐14 in patients with diffuse large B‐cell lymphoma younger than 70 years: a multicentre, prospective study

Abstract: Several studies have shown that adding rituximab to CHOP (cyclophosphamide, doxorubicin, vincristine, prednisolone) or reducing the interval between chemotherapy cycles from 3 weeks to 2 weeks improves survival in patients with diffuse large B‐cell lymphoma (DLBCL). These studies prompted our group (GOTEL) to evaluate prospectively in a pilot study the feasibility and efficacy of R‐CHOP‐14 in patients with DLBCL. Patients (<70 years) with stage II bulky or stage III or IV DLBCL and no significant comorbidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 22 publications
0
6
0
2
Order By: Relevance
“…A prospective Italian cooperative group in 50 patients with DLBCL stage II-IV and all IPI groups reported a CR/CRu rate of 74% and a 2-year actuarial EFS of 72% [14]. The results of the Spanish Oncologic Group for the Treatment and Study of Lymphomas (GOTEL) study in patients with DLBCL younger than 70 years have also recently been reported [15]. A total of 80 patients were included and 58 (73%) achieved a CR/CRu.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…A prospective Italian cooperative group in 50 patients with DLBCL stage II-IV and all IPI groups reported a CR/CRu rate of 74% and a 2-year actuarial EFS of 72% [14]. The results of the Spanish Oncologic Group for the Treatment and Study of Lymphomas (GOTEL) study in patients with DLBCL younger than 70 years have also recently been reported [15]. A total of 80 patients were included and 58 (73%) achieved a CR/CRu.…”
Section: Discussionmentioning
confidence: 88%
“…In the MSKCC 16% developed grade 2 neuropathy and 71% grade 1, and 72% of the patients received the planned dose density of vincristine [13]. In the GOTEL study, grade 3 neurotoxicity was reported in 4 patients (5%) [15]. In the RICOVER60 trial rates of grade 3-4 neuropathy varied between 7 and 11% in the 4 groups of treatment with no signifi cant differences [17].…”
Section: Discussionmentioning
confidence: 97%
“…Aynı çalışmada genel sağkalım CHOP grubunda %68'e karşılık, R-CHOP14 grubunda %78 (p= 0.018) olarak bulunmuştur (5). GOTEL grubu (Oncologico para el Tratamiento y Estudio de los Linfomas) tarafından yapılan prospektif çok merkezli bir çalışmada hastalar R-CHOP14 ile tedavi edilmiş, hastaların %73'ünde tam remisyon, ortalama 26 aylık takip süresince progresyonsuz sağkalım ve genel sağkalım oranları sırasıyla %72 ve %86 olarak saptanmıştır (6). Çalışmamızda 30 aylık takip süresince R-CHOP14 grubu hastalarda genel sağkalım %85, olaysız sağkalım %76 olarak tespit edildi.…”
Section: Tartişma Ve Sonuçunclassified
“…Elderly patients with newly diagnosed diffuse large B‐cell lymphoma (DLBCL) and a poor prognostic profile, according to the International Prognostic Index (IPI), were shown to benefit from shortening of the time interval between CHOP (cyclophosphamide, doxorubicin, vincristine and prednisone) chemotherapy cycles from 3 weeks (CHOP‐21) to 2 weeks (CHOP‐14) (Pfreundschuh et al , 2004, 2008). In these patients, biweekly CHOP plus rituximab (R) (R‐CHOP‐14) is regarded as a therapeutic standard for some cooperative groups and is a valuable option in clinical practice (Pfreundschuh et al , 2008; Rueda et al , 2008; Ziepert et al , 2010; Zwick et al , 2007).…”
mentioning
confidence: 99%